2021
DOI: 10.3390/genes12050700
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Transcriptome Analysis Reveals Enrichment of Genes Associated with Immune and Lipid Mechanisms, Favoring Soybean Meal Tolerance in High-Growth Zebrafish (Danio Rerio)

Abstract: The molecular mechanisms underlying fish tolerance to soybean meal (SBM) remain unclear. Identifying these mechanisms would be beneficial, as this trait favors growth. Two fish replicates from 19 experimental families were fed fishmeal-(100FM) or SBM-based diets supplemented with saponin (50SBM + 2SPN) from juvenile to adult stages. Individuals were selected from families with a genotype-by-environment interaction higher (HG-50SBM + 2SPN, 170 ± 18 mg) or lower (LG-50SBM + 2SPN, 76 ± 10 mg) weight gain on 50SBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Our search for indicative parameters for SBM-induced enteritis at the molecular level turned out to be more challenging than expected. The histopathological analysis suggested that molecular markers were likely to be encountered in the intestine, as supported by recent studies in various fish species [40,54,55]. However, as these investigations require the killing and dissection of the animals, we first screened for potential markers that could be detected in small blood volumes taken non-lethally from farmed fish [56].…”
Section: Discussionmentioning
confidence: 89%
“…Our search for indicative parameters for SBM-induced enteritis at the molecular level turned out to be more challenging than expected. The histopathological analysis suggested that molecular markers were likely to be encountered in the intestine, as supported by recent studies in various fish species [40,54,55]. However, as these investigations require the killing and dissection of the animals, we first screened for potential markers that could be detected in small blood volumes taken non-lethally from farmed fish [56].…”
Section: Discussionmentioning
confidence: 89%
“…LPS treatment altered the expression of some genes with known function in the reproduction system such as zp3 [107,108], as well as others in the fish gonads that have not been described previously in fish. Examples include tgfb1a function in testicular immune homeostasis in sheep [109], and cyp46a1 function in intestine after enriched diets [110] and cldn5b involvement in the blood-testis-barrier in mice [111].…”
Section: Discussionmentioning
confidence: 99%